Questioning the Colonial Imaginary: Review of Michael D. Wise, Producing Predators: Wolves, Work, and Conquest in the Northern Rockies - Wynn, Kerry (Humanimalia, 2019)
Michael D. Wise, Producing Predators: Wolves, Work, and Conquest in the Northern Rockies. Lincoln: University of Nebraska Press, 2016. 210 pp. $45.00 hc; $45.00 e-book.